Contracts, fairness, and incentives - Ernst Fehr; Alexander Klein; Klaus M. Schmidt (Center for Economic Studies and ifo Institute (CESifo), 2004)
We show experimentally that fairness concerns may have a decisive impact on both the actual and the optimal choice of contracts in a moral hazard context. Explicit incentive contracts that are optimal according to self-interest theory become inferior when some agents value fairness. Conversely, implicit bonus contracts that are doomed to fail among purely selfish actors provide powerful incentives and become superior when there are some fair-minded players. The principals understand this and predominantly choose the bonus contracts, even preferring a pure bonus contract over a contract that combines the enforcement power of explicit and implicit incentives. This contract preference is associated with the fact that explicit incentives weaken the enforcement power of implicit bonus incentives significantly. Our results are largely consistent with recently developed theories of fairness, which also offer interesting new insights into the interaction of contract choices, fairness and incentives.
Keywords: J3; C7; C9; 330; moral hazard; incentives; bonus contract; fairness; inequity aversion; Anreizvertrag; Gerechtigkeit; Theorie